Safety of Sabin-derived inactivated poliovirus vaccine in adult booster recipients: a systematic review and meta-analysis - Muhammad Hussain; Muhammad Hassan; Abdul Hannan; Arham Kamil; Muhammad Tayyab Azam; Zain Ul Abideen Shahid; Hasibullah Aminpoor; Suhaylah Gore; Faizan Ahmed; Anna Guseva (Frontiers in Public Health, 2026)
Background Poliomyelitis remains a public health concern in select regions. Sabin strain-derived inactivated poliovirus vaccine (sIPV) offers a potentially safer and cost-effective alternative to conventional IPV (cIPV) for adult booster immunization. Objective To systematically review and meta-analyze evidence on the safety of sIPV in adults. Methods We searched PubMed, Embase, Cochrane, and Scopus through January 2026 for randomized controlled trials comparing sIPV with cIPV/w-IPV or placebo in adults. Safety outcomes included local and systemic adverse events: pain, erythema, induration, fever, headache, malaise, and allergic reactions. Data extraction and risk of bias assessment were independently performed. Meta-analysis was conducted using random-effects models in RevMan 5.4, reporting risk ratios (RR) with 95% confidence intervals (CI). Evidence certainty was assessed using GRADE. Results Four trials encompassing 70–340 adults were included. Pooled analyses demonstrated no statistically significant differences in any adverse events between sIPV and cIPV: pain (RR 1.57, 95% CI 0.98–2.50), erythema (RR 1.54, 95% CI 0.64–3.69), induration (RR 0.33, 95% CI 0.04–3.06), fever (RR 0.96, 95% CI 0.39–2.33), headache (RR 0.70, 95% CI 0.21–2.37), and malaise (RR 0.75, 95% CI 0.17–3.27). Heterogeneity was negligible ( I 2 = 0%). Overall, adverse events were mild, transient, and comparable across vaccines and most included trials reported no serious adverse events (SAEs), indicating a favorable safety profile. Certainty of evidence was low to very low due to small sample sizes and imprecision. Conclusion sIPV demonstrates a safety profile comparable to conventional IPV in adult booster recipients, supporting its use as a viable alternative in polio eradication strategies. Further large-scale and long-term studies are warranted to confirm these findings. Systematic Review Registration identifier: CRD420261329648.